LIABILITY OF SHOPEE E-COMMERCE PLATFORM ACTORS FOR DAMAGE TO GOODS RECEIVED BY BUYERS IN THE PERSPECTIVE OF THE CONSUMER PROTECTION LAW AND THE ITE LAW - Chintia Natasya; Moh. Sigit Gunawan (Fakultas Hukum Universitas Swadaya Gunung Jati, 2026)
This study aims to analyze the legal provisions regarding the responsibilities of the Shopee e-commerce platform in electronic transactions based on the Consumer Protection Law and the Electronic Information and Transactions (ITE) Law, and to identify the forms of liability in the event of damaged goods received by consumers, along with any obstacles that hinder their resolution. This study uses a normative juridical research method. The results indicate that e-commerce platforms are both service providers and Electronic System Providers (ESOs). The legal provisions in this study address the responsibilities of Shopee e-commerce platform operators in Indonesia, based on the Consumer Protection Law (UUPK) as the lex generalis, the Information and Electronic Transactions Law (ITE) and Government Regulation No. 80 of 2019 concerning E-Commerce (PMSE) as the lex specialis. The implementation of these responsibilities in practice still faces various obstacles influenced by several frequently emerging barriers. Therefore, the effectiveness of digital consumer protection depends on strengthened regulatory oversight and internal systems of platform operators that support the values of fairness and transparency.